(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This descriptive study aimed to characterize the graduates of the Inter-unit Doctoral Program in Nursing of the School of Nursing of the University of São Paulo, who defended their theses in the period 1998-2008, in relation to the location they developed their Masters and their pre and post-doctoral employment, also to investigate the theses defended in relation to the thematic areas and methodological approaches used. Data were collected from the Fenix-USP System and the Lattes Curriculum System. Of the 190 graduates, 178 had curriculums available online. Of those, 58.4% performed teaching and research activities when they entered the doctoral program, which were activities mainly developed at Federal Universities (34.8%). This predominance was maintained after the conclusion of the doctoral studies. The thematic areas most studied were Womens Health (20.5%) and Adults/Elderly Health (13.2%). Regarding the methodological approach, 68.4% used qualitative methods. The data evidenced the contributions of this Program to research.